Causes and outcome of young infant admissions to a Kenyan district hospital. Issue 5 (1st May 2003) - English, M; Ngama, M; Musumba, C; Wamola, B; Bwika, J; Mohammed, S; Ahmed, M; Mwarumba, S; Ouma, B; McHugh, K; Newton, C
Abstract : Aims: To provide a comprehensive description of young infant admissions to a first referral level health facility in Kenya. These data, currently lacking, are important given present efforts to standardise their care through the integrated management of childhood illness (IMCI) and for prioritising both health care provision and disease prevention strategies. Methods: Prospective, 18 month observational study in a Kenyan district hospital of all admissions less than 3 months of age to the paediatric ward. Results: A total of 1080 infants were studied. Mortality was 18% overall, though in those aged 0–7 days it was 34%. Within two months of discharge a further 5% of infants aged <60 days on admission had died. Severe infection and prematurity together accounted for 57% of inpatient deaths in those aged <60 days, while jaundice and tetanus accounted for another 27%. S pneumoniae, group B streptococcus, E coli, and Klebsiella spp. were the most common causes of invasive bacterial disease. Hypoxaemia, hypoglycaemia, and an inability to feed were each present in more than 20% of infants aged 0–7 days. Both hypoxaemia and the inability to feed were associated with inpatient death (OR 3.8 (95% CI 2.5 to 5.8) and 7.4 (95% CI 4.8 to 11.2) respectively). Conclusions: Young infants contribute substantially to paediatric inpatient mortality at the first referral level, highlighting the need both for basic supportive care facilities and improved disease prevention strategies.